Inventarisasi Ikan Karang Famili Pomacentridae Di Terumbu Karang Pulau Kasuari Kacamatan Huamual Belakang Kabupaten Seram Bagian Barat - Sahlan Hamid; Veince B. Silahooy; Mechiavel Moniharapon (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
Coral reefs are a unique ecosystem in tropical waters that provide habitat for reef fish. The purpose of this study was to inventory the reef fish species of family Pomacentridae in Kasuari Island, Huamual Belakang District, Seram Bagian Barat Regency. This research is a quantitative descriptive study using the bell transect method. The results of this study found 16 species of 10 genera of reef fish from Pomacentridae family, namely Abudefduf sexfasciatus, Abudefduf vaigiensis, Amblygphidodon curacao, Amphiprion clarkii, Amphiprion melanotus, Chrysiptera rolandi, Chromis atripectroalis, Chromis viridis, Dascyllus aruanus, Dischistodus melanotus, Dischistodus perspicillatus, Neoglyphidodon melas, Plectroglyphidodon lacrymatus, Pomacentrus amboinensis, Pomacentrus auriventris, dan Pomacentrus philippinus.Keywords: Inventory; Reef fish; Pomacentridae; Kasuari Island